Blunt Trauma and Right Diaphragmatic Rupture: Unveiling the Impact - Alves, Duarte Gil (2023)
Traumatic diaphragmatic ruptures are rare, yet blunt injuries tend to be more easily overlooked compared to penetrating trauma. The minimal evidence of external injuries makes a high index of suspicion key for diagnosis. We report the case of a right-sided thoracoabdominal blunt trauma that resulted in a diaphragmatic rupture and fractured rib. Although often approached through a midline laparotomy, a definitive right thoracotomy repair was exceptionally performed since the adjacent peritoneum remained uninjured.